Oxidative Stress in Intestinal Ischemia-Reperfusion - Li, Guangyao; Wang, Shuang; Fan, Zhe (Frontiers in Medicine, 2022)
Ischemia-reperfusion (I/R) injury is a manifestation of tissue or organ damage that is followed by ischemia and exacerbated by the return of blood flow to a previously damaged tissue or organ. The intestines are one of the most sensitive tissues and organs to I/R injury. Moreover, the adverse consequences of intestinal I/R (II/R) injury are not limited to the intestine itself and can also lead to damage of distant tissues and organs. The mechanism of II/R is extremely complex, and oxidative stress is the key link in the pathogenesis of II/R injury. This review summarizes the roles of oxidative stress and its signaling pathways involved in II/R. The signaling pathways that mitigate II/R injury include the Nrf2-mediated signaling pathway, Wnt/β-catenin pathway and PI3K/Akt pathway; those that aggravate II/R injury include the JAK/STAT pathway, TLR receptor-mediated signaling pathway, PKCβII/p66shc pathway and miRNA/p66shc pathway; the effect of miRNA on related pathways and mitochondrial DNA translocation. the above pathways provide new ideas for further exploring the occurrence and development of II/R and more effective treatments for II/R injury.